Pengaruh Experienced Regret, Risk Tolarance, Illusion Of Control Dan Literasi Keuangan Terhadap Keputusan Investasi Cryptocurrency (Studi kasus pada Exchange Tokocrypto) - Akmal Zakaria; Liya Megawati (Peneliti.net, 2022)
This study aims to find out, analyze and explain the influence of free variables, namely Experienced regret, Risk tolarance, Illusion Off Control, and Financial literacy on variables bound by investment decisions. The sample of this study was 145 respondents domiciled in Karawang, this research was included in quantitative research and data collection methods using questionnaires with the Probality Sampling sampling technique using the Purposive Sampling method. In this study, it utilized SPSS 22 for Data Validity Test, Classical Assumption Test, and Hypothesis Test. The results of the T statistical test showed that Eperienced regret had a significantly significant negative effect on investment decisions. Risk Tolarance has a partial and positive effect on investment decisions. Illusion Off control partial signific and positive towards investing decisions . Financial Literacy has a partial and positive effect on investment decisions while the F test results show that the variables Eperienced regret, Risk Tolarance Illusion Off Control, and Financial Literacy have a significant effect on investment decisions. The value of the influence of the variables Eperienced regret, Risk Tolarance Illusion Off Control, and Financial Literacy was 57.3% while the remaining 42.7% was influenced by variables that were not studied in this study. It is known that these variables affect a person in investing, therefore the Tokocrypto company does not only educate about the fundamentals of an asset but educates about financial psychology factors as well.